Influence of bias voltage and sputter mode on the coating properties of TiAlSiN: Einfluss der Biasspannung und des Sputtermodus auf die Schichteigenschaften von TiAlSiN. Issue 9 (5th September 2017) - Tillmann, W.; Dildrop, M.
Abstract: Silicon offers promising opportunities to improve the characteristics of thin coatings. By adding silicon to TiAlN, the oxidation resistance as well as the tribological properties can be increased and improved. To analyze the influence of the silicon content on the coating properties of TiAlSiN, it is necessary to keep the ratio of the other coating elements constant by using the right target configuration. Within this study, TiAlSiN coatings were deposited on hot work steel AISI H11 by using magnetron sputtering (Cemecon CC800/9 sinox ML). This steel was previously plasma nitrided to increase the hardness and hence the carrying load of the substrate, avoiding shell egg effect during the analysis. Different sputter modes were used to analyze the possibility to produce TiAlSiN by utilizing a pure low conductive silicon target. The bias voltages were systematically varied to see their influence on the structure and chemical compositions of the coating which were investigated by means of scanning electron microscopy and energy dispersive X‐ray spectroscopy (EDX). Furthermore, the roughness of the surface of the coatings was measured by an optical three‐dimensional surface analyzer. The results of this study serve as a basis for further investigations regarding the variation of the silicon content of TiAlSiN coatings.